Strategi Keamanan Energi Tiongkok melalui Pembangunan Pipa Minyak Gwadar-Kashgar dalam Kerangka China-Pakistan Economic Corridor (CPEC) Tahun 2004-2013 - Novelia Panin, Putu Gita; Fasisaka, Idin; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT This research aims to explain China’s strategy on taking measures to build Gwadar-Kashgar oil pipeline by using qualitative method. The above-mentioned pipeline through Pakistan-China line is a response of Malacca Dilemma that vividly captures the nature of the Sea Lanes of Communication (SLoC) challenges to China’s oil transportation from the Middle East. Given the proposed pipeline is far from cost effective compare to the usual routes, China still dependent on the sea routes considering the small proportion of oil that can be transported through the pipeline. The data in this research was analysed by using energy security, national strategy and rational choice theory frameworks. This research perceives that China’s overland oil supply route plan is driven by a purpose to strengthening China’s energy security by using a minimizing the maximum lost strategy and to avoid possibility of any damage lost. Keywords: Malacca Dilemma, Sea Lanes of Communication, Energy Security, National Strategy. Rational Choice Theory.